2015
DOI: 10.1007/s00394-015-1090-z
|View full text |Cite
|
Sign up to set email alerts
|

A Western dietary pattern is associated with higher blood pressure in Iranian adolescents

Abstract: Background: Studies have shown that pre/postnatal undernutrition leads to higher risk of non communicable diseases such as diabetes, hypertension and obesity in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 64 publications
2
27
0
Order By: Relevance
“…In contrast with other studies, no differences were found regarding metabolic variables. However, those previous studies considered fried snacks and candies [49], or western dietary patterns [50][51][52][53][54]. As for anthropometry, no differences were observed between the different EDSF CF groups.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast with other studies, no differences were found regarding metabolic variables. However, those previous studies considered fried snacks and candies [49], or western dietary patterns [50][51][52][53][54]. As for anthropometry, no differences were observed between the different EDSF CF groups.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, a negative correlation was found for the prudent dietary pattern (r −576 P < 0•01). Hojhabrimanesh et al (31) also observed a significantly higher mean WC among individuals in the highest tertile of the Western pattern.…”
Section: Dietary Pattern and Bmi And Waist Circumferencementioning
confidence: 89%
“…The selected studies were conducted in Australia (22,23) , America (24)(25)(26)(27)(28) , Asia (29)(30)(31)(32)(33)(34)(35)(36) , Europe (37)(38)(39) and Africa (40) . Most were cross-sectional studies, and only two were cohort studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reasonable explanations which create a link between diet patterns and chronic diseases risk. There is convincing evidence that dietary habits can affect cardio-metabolic risk factors including blood pressure (62,63) , lipid profile (64) , insulin resistance (65) , endothelial function (66) , oxidative stress (67) and systemic inflammation (68) . In addition, a recent meta-analysis of cross-sectional studies suggested that higher adherence to healthy dietary patterns may decrease the risk of central fatness (69) .…”
Section: Discussionmentioning
confidence: 99%